The Effect of Return on Assets and Return on Equity Toward Changes in The Price of Transportation Companies (International Journal of Psychosocial Rehabilitation, 2020)
This research purposes to examine the return on assets (ROA) effect’s and return on equity's (ROE) on changes in share prices listed on the ISX at the 2015-2018 period. The method used in this research’s explanatory research. The data used is secondary. The population at this research's all sub-sector of transportation companies listed at the ISX for the period of 2015-2018. Sampling using a purposive method, so the number of samples obtained by 11 corporations with a total observation of 44 data. The analysis of data method uses analysis of panel data, and data testing is done using the Eviews 8 program. The results showed that ROA partially had no effect on changes in stock prices. ROE affects the changes in stock prices. With a determination coefficient’s (R2) of 0.217053, which denotes that the variability of the dependent variable, that is, changes in stock prices, can be explained by the variables of independent specific return on assets and return on equity in this study amounted to 21.7053%, and the remaining 78.2947% is explained by others than the research model.